Investigating the mechanism of inositol against paclitaxel chemoresistance on triple-negative breast cancer by using 7T multiparametric MRI and mitochondrial changes - Wentao Xuan; Wangmin Li; Lixin Ke; Yuanyu Shen; Xiaolei Zhang; Yue Chen; Zhiliang Ye; Caiyu Zhuang; Shiyan Xie; Renhua Wu; Yan Lin (Breast Cancer Research)
Abstract Background The emerging triple-negative breast cancer (TNBC) treatments target mitochondrial fission to combat paclitaxel (PTX) resistance. Inositol’s inhibition of this process makes it a potential therapy. Multiparametric MRI provides an early and effective assessment of these innovations. Objective To monitor the efficacy of Inositol on PTX-resistant TNBC mice using 7T multiparametric MRI, and to further explore the mechanism of inositol inhibiting PTX chemoresistance in combination with the morphological changes of isolated mitochondria. Materials and methods BALB/c mice aged 6–8 weeks were subcutaneously inoculated with PTX-resistant 4T1 cells and divided into three groups: PTX-treated mice (n = 24), “PTX + Inositol”-treated mice (n = 24) and untreated mice (n = 24). Six mice in each group underwent diffused weighted imaging (DWI) and diffusion kurtosis imaging (DKI) every 7 days after administration. To observe the dynamic changes of inositol within the tumor tissue post-treatment, chemical exchange saturation transfer (CEST) imaging was performed. Six mice in each group were sacrificed on day 0, 7, and 14 respectively for histopathological examination. After a 3-week scanning cycle, the remaining mice in each group were euthanized for histopathological analysis. The therapeutic response of inositol was assessed via Hematoxylin & Eosin (H&E) staining and Ki-67 immunohistochemistry. The effects of inositol on mitochondrial structure and PTX resistance were studied by Western Blot and electron microscopy. One-way analysis of variance, independent samples t-test, paired samples t-test, Kruskal-Wallis, and Spearman rank correlation were used. Results The CEST signal of inositol in tumor tissue was significantly higher after 1 h of inositol administration than before (2.75 ± 0.71% vs. 1.80 ± 0.33%, p < 0.05). On day 21 after treatment, the tumor volume in the PTX + Ins group was smaller than that in the PTX group (191.52 ± 27.98 mm3 vs. 388.98 ± 32.62 mm3, p < 0.001). The MD, MK, and ADC values were correlated significantly with tumor cell density (MD, r = -0.872; MK, r = 0.723; ADC, r = -0.858) and Ki-67 level (MD, r = -0.975; MK, r = 0.680; ADC, r = -0.860). The p-AMPK levels of PTX + Ins group were lower than that of PTX group (0.50 ± 0.06 vs. 0.60 ± 0.05, p = 0.04), and the mitochondrial length was longer than that of PTX group (0.86 ± 0.10 vs. 0.44 ± 0.09, p < 0.001), with a significant correlation to Ki-67 levels (r = -0.853, p < 0.001). Conclusion Inositol may counteract PTX resistance in TNBC by disrupting mitochondrial fission, and DWI combined with DKI effectively tracked this effect.